PHARMACOKINETIC STUDY OF HY-FOLIC® AND FOLIC ACID IN HEALTHY VOLUNTEERS - NAFRIALDI, NAFRIALDI; SUYATNA, FRANSISCUS D. (International Journal of Applied Pharmaceutics, 2024)
Objective: HY-FOLIC® is the active form of Folic Acid (FA) produced by PT Simex Pharmaceutical Indonesia containing (6S)-5-Methyltetrahydrofolate (5-MTHF). We evaluated the pharmacokinetic profiles of HY-FOLIC® versus FA after single oral administration in healthy volunteers. Methods: A randomized, open-label, 2-way crossover, single-dose design was conducted on 12 healthy subjects with two steps. In the first step, 6 subjects were given 1100 mcg of HY-FOLIC®(1.3 μmol), and 6 subjects were given an equimolar dose of 600 mcg of FA (1.3 μmol) in a fasting condition. Blood samples were taken before, and at 1, 2, 3, 4, 5, 6, 7, and 8 h after administration of products for measurement of peak concentration (Cmax), the Area Under the Curve at t-time (AUCt) and infinite time (AUCinf). After a washout period of 14 d, the same procedure was repeated in which the first 6 subjects received FA, and the second 6 subjects received HY-FOLIC®. Pharmacokinetic data of 5-MTHF and Unmetabolized Folic Acid (UMFA) were compared with paired t-tests. Results: Cmax of 5-MTHF (mean±SD) following administration of HY-FOLIC®and FA were 46.91+28.16 vs 22.61+15.73 nmol/l, respectively (p=0.000); the AUCt were 214.47+183.46 vs 112.93+112.11 h. mmol/l (p=0.001). Conversely, Cmax of UMFA were 9.49+7.89 vs 21.97+14.79 nmol/l (p=0.003); AUCt 33.29+39.34 vs 78.16+58.93 h. nmol/l (p=0.001). Conclusion: HY-FOLIC®is much more bioavailable than FA as indicated by much higher Cmax and AUCt of the active form of 5-MTHF.